Tailored nanodisc immobilization for one‐step purification and reconstitution of cytochrome P450: A tool for membrane proteins' hard cases. Issue 18 (6th August 2021) - Zhao, Lan; Tao, Jiaoli; Huang, Yongdong; Zhu, Kai; Du, Yuxiang; Hao, Dongxia; Liu, Hongying; Zhang, Rongyue; Ma, Guanghui
Abstract: A novel nanodisc‐based immobilization method was developed for high‐efficient purification and reconstitution of cytochrome P450 in one step. Using membrane scaffold protein containing a histidine tag, charged‐nanodiscs were prepared in the form of self‐assembly of lipid‐protein nanoparticles. Their properties including the particle diameter and its distribution and Zeta potential were controlled well by adjusting molar ratios of phospholipids to membrane scaffold protein. At an optimum lipid‐to‐membrane scaffold protein molar ratio of 60:1, uniformly regular‐shaped and discoidal nanodiscs with an average particle diameter of 10 nm and Zeta potential of –19 mV were obtained. They can be well fractionated by size exclusion chromatography. Charged‐nanodiscs were successfully immobilized onto Ni‐chelating microspheres via histidine tags with a density of 6.6 mg membrane scaffold protein/mL gel. After being packed in a column, chromatography studies demonstrated that this nanodisc‐immobilized chromatographic medium had a specific binding to cytochrome P450 in rat liver microsome. Nanodiscs containing cytochrome P450 can be furthermore eluted from the column with a diameter of about 87.0 nm and height of about 8.0 nm, respectively. The purity of cytochrome P450 after purification increased 25 folds strikingly. This nanodisc‐immobilized chromatography method is promising for the one‐step purification and reconstitution of membrane protein.